Application of Experimental Design Methodology for Adsorption of Brilliant Blue onto Amberlite XAD-4/Agaricus campestris as a New Biocomposite Adsorbent - Ahmed, Ahmed A.; Yönten, Vahap (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
This research presents a new biocomposite adsorbents using response surface methodology (RSM) to find the best conditions for highest adsorption of Brilliant Blue G250 (BBG) from aqueous solution by Amberlite XAD-4/Agaricus campestris. The most effective parameters are determined by Plackett–Burman design (PBD) with specific ranges initial dye concentration (5–150 mg.L-1), temperature (20–50°C), contact time (5–100 min), pH (3–11), shaking speed (150–300 rpm), sample volume (5–75 mL), and adsorbent dosage (0.05–0.6 g). Then, in the second step, the optimum condition of effective factors is predicted using steepest ascent design. Finally, optimal medium conditions of effective parameters with central composite design are located. According to RSM, the best adsorbent amount, contact time, initial dye concentration, and sample volume for maximum removal% of BBG (96.72%) are 0.38 g, 60.78 min, 107.13 mg.L-1, and 28.6 mL, respectively. The adsorption of brilliant blue is approved by scanning electron microscopy. Under optimum conditions, it is concluded that XAD4/A. campestr is biocomposite is a suitable adsorbent for removing BBG from aqueous solution.